A patient who made an impact on how I practice: Severe leptospirosis presenting as ARDS in the ICU - Evangelia S. Panagiotidou; Sofia V. Akritidou; Seraphim T. Kotoulas; Evdokia K. Sourla; Basilis G. Mpikos; Basilis P. Bagalas; Ioannis T. Stanopoulos; Katalin M. Fekete; Athanasia D. Pataka (Elsevier, 2018)
Severe leptospirosis can be a rare cause of acute respiratory distress syndrome (ARDS) and multiorgan failure. A patient who made an impact on how I practice was a case of severe leptospirosis (Weil's disease) that presented as ARDS in the ICU. Leptospirosis is an under-reported infectious disease worldwide and should be considered as a cause of ARDS especially in patients with exposure history complicated with diffuse alveolar bleeding (DAH), icteric hepatitis and renal deterioration. Empiric treatment should be recommended before confirmation of laboratory tests as serological diagnosis is time consuming. Keywords: Leptospirosis, ARDS, Alveolar bleeding, Icteric hepatitis, Renal failure